Pricing Multivariate European Equity Option Using Gaussians Mixture Distributions and EVT-Based Copulas - Hassane, Abba Mallam; Diakarya, Barro; WendKouni, Yam´eogo (Hindawi, 2021)
In this article, we present an approach which allows taking into account the effect of extreme values in the modeling of financial asset returns and in the valorisation of associated options. Specifically, the marginal distribution of asset returns is modelled by a mixture of two Gaussian distributions. Moreover, we model the joint dependence structure of the returns using a copula function, the extremal one, which is suitable for our financial data, particularly the extreme values copulas. Applications are made on the Atos and Dassault Systems actions of the CAC40 index. Monte Carlo method is used to compute the values of some equity options such as the call on maximum, the call on minimum, the digital option, and the spreads option with the basket (Atos, Dassault systems) as underlying.
International Journal of Mathematics and Mathematical Sciences, 2021, 1-9.
Keywords: Saley Bisso; CEFORGRIS; Université Joseph Ki-Zerbo; Burkina-Faso